2014
DOI: 10.31387/oscm0160099
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Collaboration and Trust in the Philippines

Abstract: This paper presents the relationship between supply chain collaboration and trust, two important concepts in supply chain management. The transaction costs and stakeholder theories were used as frameworks in analyzing supply chain collaboration and trust. These constructs were developed through literature review and in consultation with industry experts. Factor analysis was conducted to identify the underlying dimensions of these constructs while correlation analysis was done to determine their association. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
1
5
0
1
Order By: Relevance
“…As most members of clusters belong to WSCC (55) and MSCC (19), it implies that overall level of collaboration practice is not good. Talavera (2008) observed a similar finding (in different settings) and found the practice of collaboration at a very low level.…”
Section: Good Supply Chain Collaborationsupporting
confidence: 71%
See 1 more Smart Citation
“…As most members of clusters belong to WSCC (55) and MSCC (19), it implies that overall level of collaboration practice is not good. Talavera (2008) observed a similar finding (in different settings) and found the practice of collaboration at a very low level.…”
Section: Good Supply Chain Collaborationsupporting
confidence: 71%
“…Demand forecast information, available inventory, holding cost and technology and machinery are a few of the important resources required for effective and timely production. The demand forecast is important (Daugherty et al, 2006;Simatupang and Sridharan, 2004;Talavera, 2008) as it provides prior knowledge of the expected level of customer demand. The more accurate is the forecast, the better will be the production and operations management systems.…”
Section: Operational Resource Sharingmentioning
confidence: 99%
“…Pakistan bağlamında, müdürler toplumun katılımını olumsuz bir durum olarak görmekte (Ahmad ve Bin Said, 2013) ve veliler ile toplumun yönetim sorunları yaratabileceğine inanmaktadır. Bu durumun aksine, bir kurumunfarklı paydaşlarla olan ilişkisi o kurum için bir varlıktır (Talavera, 2008). Söz konusu durumda bu varlık öğrencinin akademik başarını artırır ve okul üyelerini motive eder (Ahmad ve Bin Said, 2013).…”
Section: Discussionunclassified
“…More accuracy in demand forecast results in better production and operations in the SC. Talavera (2008), Ann Vereecke and Muylle (2006) and Daugherty et al (2006) suggested that the sharing of inventory-related information has positive effects on operations and performance (Nakano, 2009;Ann Vereecke and Muylle, 2006;. It also helps in deploying resources in an effective way that creates value and competition (Fawcett, 2010;Lorentz, 2008).…”
Section: Operational Resource Sharingmentioning
confidence: 99%